Higher HEI-2015 score is associated with reduced risk of fecal incontinence: insights from a large cross-sectional study - Zhuhui Zhang; Pengfei Wang; Guoce Cui; Huashan Li (BMC, 2024)
Abstract Objective Diet habit plays a vital role in fecal incontinence (FI) progression. However, it remains unknown whether dietary quality is related to FI. Our study sought to explore the relationship between healthy eating index-2015 (HEI-2015) score and FI among US adults. Methods An analysis of data from the 2005-2010 National Health and Nutrition Examination Survey was conducted in our study. The Bowel Health Questionnaire defined FI as losing liquid, solid, or mucus stool at least monthly. The diet's quality was evaluated using HEI-2015 score. The odds ratios (ORs) and 95% confidence interval (95%CI) were calculated using multi-variable logistic regression models. Results There were 11,452 participants, with 9.3% (1062/11452) who experienced FI. Compared with individuals with inadequate group (HEI score < 50), the adjusted OR values for HEI score and FI in average group (50 ≤ HEI score < 70) and optimal group (HEI score ≥ 70) were 0.89 (95%CI: 0.74-1.07, p = 0.214) and 0.69 (95%CI: 0.52-0.91, p = 0.011), respectively. Subsequent stratified analyses did not reveal any interactions. Conclusions High-quality diets are related with a lower risk of FI. Therefore, it is imperative to take into account the potential impact of diet on FI when devising strategies for the treatment and prevention.